2020
DOI: 10.1111/sji.12971
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and scavenger receptors in obesity‐associated non‐alcoholic liver fatty disease (NAFLD)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…We also analyzed macrophages in the liver as previous study has demonstrated that inflammation and monocyte recruitment is involved in steatohepatitis [21,22] and macrophages might be the mediators and drivers of chronic low-grade inflammation in NAFLD. [23] Staining of F4/80, a widely used macrophage marker, revealed that the macrophage infiltration in the liver was elevated by HFHSD, while such elevation was reversed by the FMD administration (Figure 4F). In addition, we analyzed the mRNA levels of a few representative inflammation markers in the liver tissue.…”
Section: Intermittent Application Of the Fmd Reduces Hepatic Steatosis And Macrophage Infiltration In Nafld Mouse Modelmentioning
confidence: 99%
“…We also analyzed macrophages in the liver as previous study has demonstrated that inflammation and monocyte recruitment is involved in steatohepatitis [21,22] and macrophages might be the mediators and drivers of chronic low-grade inflammation in NAFLD. [23] Staining of F4/80, a widely used macrophage marker, revealed that the macrophage infiltration in the liver was elevated by HFHSD, while such elevation was reversed by the FMD administration (Figure 4F). In addition, we analyzed the mRNA levels of a few representative inflammation markers in the liver tissue.…”
Section: Intermittent Application Of the Fmd Reduces Hepatic Steatosis And Macrophage Infiltration In Nafld Mouse Modelmentioning
confidence: 99%
“…Scavenger receptors comprise another prototypical class of different surface receptors that recognize and internalize OSEs ( 67 ). Similar to TLRs, scavenger receptors bind oxidized and non-native LDL particles and contribute to the activation of macrophages in the context of inflammation ( 67 , 75 ). There are many different types of scavenger receptors, including CD36, scavenger receptor type A1 (SR-A1), SR-A2, SR-B1, CD68, and lectin-like oxidized LDL receptor 1 (LOX1) ( 67 ).…”
Section: Immune Recognition Of Oxidation-specific Epitopesmentioning
confidence: 99%
“…Resistin can increase the uptake of oxidised lowdensity lipoprotein by macrophages through their scavenger receptors, thereby promoting foamy cell formation in vitro, suggesting that HPCs influence macrophage function [70][71][72] . Recently, our group showed that the formation of foamy macrophages in human NAFLD is mediated by the macrophage scavenger receptor 1, resulting in the release of pro-inflammatory cytokines, such as TNFa, but also inducing metabolic changes in the liver [73,74] . Adiponectin, on the other hand, is regarded as an anti-inflammatory modulator in NAFLD and is protective against HCC formation [69,75] .…”
Section: Hepatic Progenitor Cell Secretomementioning
confidence: 99%